2017
DOI: 10.1111/ppe.12417
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Risk of Pregnancy Loss Among US Women, 1990–2011

Abstract: Background: Pregnancy loss can have physical and psychological consequences for women and their families. Though a previous study described an increase in the risk of self-reported pregnancy loss from 1970 to 2000, more recent examinations from population-based data of US women are lacking. Methods: We used data from the 1995, 2002,[2006][2007][2008][2009][2010][2011][2012][2013][2014][2015] National Survey of Family Growth on selfreported pregnancy loss (miscarriage, stillbirth, ectopic pregnancy) among US wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
102
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 34 publications
(95 reference statements)
14
102
2
6
Order By: Relevance
“…The rate of congenital malformation reported in neonates born to mothers treated with eculizumab lies within the range of that reported in the general population (UK Teratology Information Service, ). In addition, the overall rate of miscarriage in this study (15·8%) was similar to the rate of pregnancy loss observed in a population of more than 20 000 women in the United States from 1990 to 2011 (19·7%) (Rossen et al , ). Thus, the use of eculizumab in pregnancy in patients with PNH or aHUS may be appropriate and safer than discontinuing or not initiating eculizumab treatment.…”
Section: Discussionsupporting
confidence: 87%
“…The rate of congenital malformation reported in neonates born to mothers treated with eculizumab lies within the range of that reported in the general population (UK Teratology Information Service, ). In addition, the overall rate of miscarriage in this study (15·8%) was similar to the rate of pregnancy loss observed in a population of more than 20 000 women in the United States from 1990 to 2011 (19·7%) (Rossen et al , ). Thus, the use of eculizumab in pregnancy in patients with PNH or aHUS may be appropriate and safer than discontinuing or not initiating eculizumab treatment.…”
Section: Discussionsupporting
confidence: 87%
“…This risk is remarkably similar to reports from other Nordic countries (range of 13% to 14%) 567. Estimates from the United States and Canada were more variable (range of 9% to 20%) 234. This consistency with other Nordic studies, and with prospective studies with full ascertainment of early miscarriages, provides some reassurance that the Norwegian registries capture most recognised miscarriages.…”
Section: Discussionsupporting
confidence: 85%
“…In 2010, an estimated 48.5 million couples worldwide were infertile, with little changes over the previous two decades (7). Early pregnancy loss (frequently before 13 weeks of gestation) is estimated to occur in 15-20% of recognized pregnancies, without major geographical differences (8)(9)(10). Of note, morbidity and pregnancy complications at more advanced stages of gestation (e.g., preeclampsia, preterm labor and stillbirth) often have a higher burden in low-resources settings, especially in south Asia and sub-Saharan Africa (11).…”
Section: Global Burden Of Pregnancy Complicationsmentioning
confidence: 99%